Tele-Psychiatry during COVID-19 at HMC Peshawar - Akhunzada, Wajid Ali; Laghari, Darya Khan; Rasheed , Hooria; Abbas, Amer; Hameed, Nadia; Ayub, Sara; Mughal, Huma (Journal of Liaquat University of Medical & Health Sciences, 2023)
Objective: The main objectives of the current study were to find out the frequencies of Psychiatric disorders in the general population during COVID-19 and to compare the gender-based association between newly diagnosed patients during COVID-19 with already existing psychiatric patients in Peshawar to provide patient care on priority bases. Methodology: This Cross-sectional design study was carried out in the Department of Psychiatry and Behavioral Sciences, HMC/MTI, from May to August 2020. Those patients who approached psychiatry OPD through video/audio online calls and could understand and respond to suggestions were included. The bio-data was collected, and DSM-5 criteria were used for diagnosis. Descriptive statistics were used for statistical significance, and the statistical package of social sciences (SPSS-21) was used for analysis and results. Results: The results findings of the current study revealed that 59.3% of the patients approached for telepsychiatry consultation were from the district of Peshawar. Among them, 54% were female, and most patients were young married females (50.7%) with no job outside the home. The finding further revealed that most of the sample affected by psychiatric illness were uneducated (31.3%) and unemployed (28%). Furthermore, in the present findings, 46% of patients were diagnosed with depression, and 12% had Dissociative disorders. Conclusion: It is concluded from the present study that in the Covid-19 Pandemic, primarily females who were married with no job description are more vulnerable to psychiatric illness. Furthermore, during Covid-19 mostly cases were reported with depression and dissociative disorders.